2008
DOI: 10.1097/ede.0b013e3181883d43
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Asiatic Vibrio Diseases in South America in Phase With El Niño

Abstract: These findings identify the El Niño episodes as a reliable vehicle for the introduction and propagation of Vibrio pathogens in South America. The movement of oceanic waters seems to be one of the driving forces of the spread of Vibrio diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 41 publications
5
74
0
10
Order By: Relevance
“…However, this study has revealed that potential pathogenic strains are not rare in offshore zooplankton and that they represent a relevant fraction of the mesozooplankton microbiome. Although zooplankton has been previously proposed as a carrier and vehicle for the dispersal of cholera (Lipp et al, 2002) and pathogenic V. parahaemolyticus (Martinez-Urtaza et al, 2008a, the results of the present study represent one of the first empirical indications that virulent populations can survive in open sea conditions. The analysis of the population structure of trhpositive strains used to track the dispersal of Vibrio populations has also revealed a specific pattern of seasonal partitioning marked by distinctive populations that occur during different periods of the year.…”
Section: Discussionmentioning
confidence: 68%
“…However, this study has revealed that potential pathogenic strains are not rare in offshore zooplankton and that they represent a relevant fraction of the mesozooplankton microbiome. Although zooplankton has been previously proposed as a carrier and vehicle for the dispersal of cholera (Lipp et al, 2002) and pathogenic V. parahaemolyticus (Martinez-Urtaza et al, 2008a, the results of the present study represent one of the first empirical indications that virulent populations can survive in open sea conditions. The analysis of the population structure of trhpositive strains used to track the dispersal of Vibrio populations has also revealed a specific pattern of seasonal partitioning marked by distinctive populations that occur during different periods of the year.…”
Section: Discussionmentioning
confidence: 68%
“…La aparición y dispersión de casos en Perú en 1997 siguió el mismo patrón de dispersión que la epidemia de cólera en 1991. La aparición de estas dos epidemias de V. parahaemolyticus y V. cholerae coincidieron con el inicio de los eventos del Fenómeno del Niño de 1991 y 1997 (14) .…”
Section: Brote De Vibrio Parahaemolyticus En El Norte De Perúunclassified
“…La salinidad es un factor crítico que regula la distribución de las distintas especies de Vibrio en función de su afinidad u óptimo osmótico. De esta forma, se conoce que V. cholerae tiene afinidad por aguas más salobres que V. parahaemolyticus, lo que hace que su distribución a lo largo de las zonas costeras y estuarios esté en función de los gradientes de salinidad existentes (7) .…”
Section: Los Factores Ambientales Y Las Infecciones Por Vibriounclassified
“…Un claro ejemplo de estas variaciones en los patrones de circulación oceánica es la inversión de las corrientes en la zona ecuatorial durante el fenómeno de El Niño, con su correspondiente impacto biológico en la zona costera del Pacífico de Sudamérica y en el clima a nivel local y mundial, afectando a zonas tan distantes como África, en aspectos a priori no relacionados, como la distribución de vectores de transmisión de enfermedades. Este es el caso del fenómeno de El Niño que recientemente ha sido relacionado directamente con la dispersión y aparición de enfermedades infecciosas como el cólera y la gastroenteritis causada por V. parahaemolyticus (7,8) (Figura 1).…”
Section: Los Factores Ambientales Y Las Infecciones Por Vibriounclassified
See 1 more Smart Citation